(untitled) (Sahel Journal of Life Sciences FUDMA, 2026)
This study evaluated the fertility-enhancing effects of the ethanol stem root extract of Ozoroa insignis in female rats. The oral acute toxicity (LD50) was assessed following OECD 425 (2008) guidelines and determined to be greater than 5000 mg/kg in mice, suggesting that the extract is relatively non-toxic. Phytochemical screening based on the Trease and Evans (1996) method revealed the presence of flavonoids, alkaloids, saponins, carbohydrates, and cardiac glycosides. The fertility potential was evaluated using the ovulation induction method. In the experimental study, administering the extract at doses of 100, 200, and 400 mg/kg body weight in both pre-mating and continuous treatment groups resulted in a significant (p < 0.05) dose-dependent increase in fertility rates and a greater number of pups compared to the control group (distilled water). The highest number of pups was observed in the continuous treatment group receiving 400 mg/kg of the extract, which yielded results nearly comparable to that of the positive control group (Clomiphene citrate). These findings suggest that the ethanol stem root extract of O. insignis possesses some fertility-enhancing activity and is relatively safe at the tested doses.